Classroom Management Approaches of Religious Education Teachers: An Ethnomethodological Study - Baltacı, Ali (DINBILIMLERI AKAD ARASTIRMA MERKEZI, 2019)
Classroom management, which is the area where teachers face the most problems in their professional life, is also an essential problematic area for religious education. The aim of this study is to determine the in-class experience of religious education teachers who are working in primary, secondary and high schools with classroom management approaches and practices in a qualitative way and to determine the issues that teachers need in terms of classroom management. This study was designed according to the ethnometodological approach, which is one of the qualitative research methods. The study group consisted of 43 religious teachers working in Ankara, Antalya, Istanbul, and Mus provinces. Critical situation sampling and maximum diversity sampling were used in the selection of the participants in the study group. At the end of the research, five main themes related to classroom management were determined: physical environment, first days in class, class rules, unwanted student behaviors and parent relations. In addition, the majority of the religious education teachers prefer traditional classroom management approaches; It was determined that they tried to manage the class mostly in the reactive and preventive model and used reactive and preventive coping strategies. Unwanted behaviors, indifference to the religious courses, behaviors that impair course flow and serious behavior problems are in frequently faced problems in classroom management. Even though religion lessons are generally of interest to the students, in some cases teachers have problems in increasing the interest of students.
Keywords: Religious Education; Classroom; Classroom Management; Teacher